The chemical, sensory properties and population of lactic acid bacteria of cangkuk made from beef meat and kepayang endosperm (Pangium edule Reinw) at various fermentation times - Mirdhayati Irdha; Aprilla Felia; Rahmadani Rizki; Febrina Dewi; Irawati Evi; Saleh Eniza; Juliantoni Jepri; Adelina Triani (BIO Web of Conferences, 2024)
Cangkuk is a traditional fermented beef from Indonesia, especially Riau Province, as a specific food where the processing varies according to the ingredients, formulation, and incubation times. Kepayang endosperm is one of the materials used which contain organic acids, tannins, and polyphenol. However, research on beef fermented with addition of kepayang endosperm is still rare. This research was carried out to study the effect of fermentation times to fermented beef in terms of chemical properties, sensory test, and the population of lactic acid bacteria (Lab). A completely randomized design was performed with fermentation time as a treatment, namely: 0 day, 7 days, 14 days, 21 days, and 28 days. Data were analyzed statistically by analysis of variance. The result showed that the fermentation times up to 28 days have no significant effect to nutritional content, and populations of Lab, but significantly increased sensory properties (color, aroma, texture and taste) and could decreased the pH, total titratable acidity (TTA) and panelist acceptance. It can be concluded that fermentation time up to 28 days in processing of fermented beef could maintain nutritional content, populations of Lab, decrease pH, TTA and have good sensory properties.